Parylene-bonded micro-fluidic channels for cryogenic experiments at superfluid He-4 temperatures - Midlik, Š; Gablech, I; Goleňa, M; Brodský, J; Schmoranzer, D (The Review of scientific instruments, 2024)
We present the manufacturing process of a (24.5 × 100) μm2-sized on-chip flow channel intended for flow experiments with normal and superfluid phases of 4He and showcase such a proof-of-concept experiment. This work proves the suitability of chip-to-chip bonding using a thin layer of Parylene-C for cryogenic temperatures as a simpler alternative to other techniques, such as anodic bonding. A monocrystalline silicon chip embeds the etched meander-shaped micro-fluidic channel and a deposited platinum heater and is bonded to a Pyrex glass top. We test the leak tightness of the proposed bonding method for superfluid 4He, reaching temperatures of ≈1.6 K and evaluate its possible effects on flow experiments. We demonstrate that powering an on-chip platinum heater affects the superfluid flow rate by local overheating of a section of the micro-fluidic channel.